Role of Rab3 GDP/GTP Exchange Protein in Synaptic Vesicle Trafficking at the Mouse Neuromuscular Junction - Tanaka, Miki (The American Society for Cell Biology, 2001)
The Rab3 small G protein family consists of four members, Rab3A, -3B, -3C, and -3D. Of these members, Rab3A regulates Ca(2+)-dependent neurotransmitter release. These small G proteins are activated by Rab3 GDP/GTP exchange protein (Rab3 GEP). To determine the function of Rab3 GEP during neurotransmitter release, we have knocked out Rab3 GEP in mice. Rab3 GEP−/− mice developed normally but died immediately after birth. Embryos at E18.5 showed no evoked action potentials of the diaphragm and gastrocnemius muscles in response to electrical stimulation of the phrenic and sciatic nerves, respectively. In contrast, axonal conduction of the spinal cord and the phrenic nerve was not impaired. Total numbers of synaptic vesicles, especially those docked at the presynaptic plasma membrane, were reduced at the neuromuscular junction ∼10-fold compared with controls, whereas postsynaptic structures and functions appeared normal. Thus, Rab3 GEP is essential for neurotransmitter release and probably for formation and trafficking of the synaptic vesicles.